2016
DOI: 10.1016/j.aller.2015.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an educational programme with workshops for families of children with food allergies

Abstract: The face-to-face workshops, which included utilisation of educational materials, had positive results in terms of learning as well as in levels of satisfaction in participating families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…They reported a significant increase in knowledge scores at post‐test, concluding that the provision of information via media outlets was effective. Three studies presented information through varying formats: one through running two face‐to‐face workshops, another through showing participants’ educational videos and the final through providing engagement with a 2‐week online programme (consisting of interactive question and answer sessions and discussion threads) 10,28,30 . Despite the variation in presentation format and length of intervention, all studies reported increases in food allergy knowledge in participants between pre‐test and post‐test measures, as well as reported high levels of satisfaction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They reported a significant increase in knowledge scores at post‐test, concluding that the provision of information via media outlets was effective. Three studies presented information through varying formats: one through running two face‐to‐face workshops, another through showing participants’ educational videos and the final through providing engagement with a 2‐week online programme (consisting of interactive question and answer sessions and discussion threads) 10,28,30 . Despite the variation in presentation format and length of intervention, all studies reported increases in food allergy knowledge in participants between pre‐test and post‐test measures, as well as reported high levels of satisfaction.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 15 studies involving 6511 participants, seven were conducted in the United States, 10,11,[20][21][22][23][24] three in the United Kingdom, [25][26][27] three in mainland Europe, [28][29][30] one in Canada 31 and one in Australia. 32 Eight used a single-group pre-test/post-test design, 10,11,21,22,27,28,30,32 and four used a single-group post-test design. 23,24,29,31 Two studies used an RCT design, 20,25 and one used a non-random case-control design.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 6 ] Group-based interventions have provided positive outcomes with respect to parental psychological distress and satisfaction. [ 16 , 17 ] Family workshops, such as those for educating the families of children with food allergies, [ 39 ] changing dietary and physical activity habits in low-income families, [ 40 ] supporting children with autism and other disabilities, [ 17 ] and integrating pediatric mental health care, [ 41 ] have provided knowledge, comfort, and satisfaction for many families. To our knowledge, we are the first to design a family-centered workshop conducted by parents alongside health and education professionals for children younger than 3 years with developmental delays.…”
Section: Discussionmentioning
confidence: 99%
“…This program was run in 2 modalities: online and in-person [7]. The present article analyzes the results of the online program.…”
Section: Introductionmentioning
confidence: 99%